2007
DOI: 10.1002/aoc.1197
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, and activity of (PhCH2NH2)2CuCl2 for oxidative coupling of 2‐naphthylamine

Abstract: (PhCH 2 NH 2 ) 2 CuCl 2 (2), an effective oxidation reagent for oxidative coupling of 2-naphthylamine (1) to form 2,2 -diamino-1,1 -binaphthyl (4), is studied. Oxidative coupling of 2-naphthylamine (1) is carried out at room temperature in methanol by (PhCH 2 NH 2 ) 2 CuCl 2 (2), which is prepared from CuCl 2 ·2H 2 O and benzylamine in methanol, to give a novel copper complex, [{1,1 -(C 10 H 6 ) 2 -2,2 -(NH 2 ) 2 } 2 CuCl]Cl·CH 3 OH·3H 2 O (3), in good yield. Treatment of 3 with aqueous HCl (37%), followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Adding benzylamine in slight excess to cluster I first led to a green material (compound 1 , Figure 3) that could be structurally characterized. As primarily expected [Cu(L 1 ) 2 Cl 2 ] ( 1 ) is formed that has been described previously 7. If benzylamine was added in a large excess compound 2 formed, a blue complex (Figure 3) that could be structurally characterized and turned out to be octahedral [Cu(L 1 ) 4 Cl 2 ].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Adding benzylamine in slight excess to cluster I first led to a green material (compound 1 , Figure 3) that could be structurally characterized. As primarily expected [Cu(L 1 ) 2 Cl 2 ] ( 1 ) is formed that has been described previously 7. If benzylamine was added in a large excess compound 2 formed, a blue complex (Figure 3) that could be structurally characterized and turned out to be octahedral [Cu(L 1 ) 4 Cl 2 ].…”
Section: Resultssupporting
confidence: 74%
“…Due to our interest in copper complexes and their reactivity towards dioxygen6 we had started to investigate the reaction of copper(II) salts with different amines. When reacting CuCl 2 ⋅ 2 H 2 O with benzylamine (L 1 ) we expected to obtain [Cu(L 1 ) 2 Cl 2 ], a simple copper amine complex that had been structurally described previously 7. However, when characterizing our product we observed that by chance a polynuclear copper complex had formed similar to previous investigations on different systems 1f.…”
Section: Resultssupporting
confidence: 70%
“…The average distance (2.233(1) Å) of Cu-Cl is slightly shorter than that found in (PhCH 2 NH 2 ) 2 CuCl 2 (2.429(2) Å) [38], and the average distance (2.041(2) Å) of Cu-N is close to that found in (PhCH 2 NH 2 ) 2 CuCl 2 (1.983(3) Å) [38]. The bond angle (93.2(1)°) of Cl(1)-Cu(1)-Cl(2) is smaller than that found in (PhCH 2 NH 2 ) 2 CuCl 2 (108.9(1)°) [38]. The torsion angle between the naphthalene rings is 68.3(3)°, which is smaller than that found in 1 (75.6(3)°).…”
Section: Synthesis and Characterization Of Cu(ii) Complexes 42-45mentioning
confidence: 54%
“…Treatment of AgX (X = NO 3 , PF 6 , OTf) with 1 equiv of chiral N 4 -ligands 5, 7, 8 and 10 in mixed solvents of MeOH and CH 2 Cl 2 (1:4) gives the chiral binuclear, ionic Ag(I) complexes [Ag 2 (5) 2 ]X 2 (X = NO 3 (24), PF 6 (25), OTf (26)), [Ag 2 (7) 2 ]X 2 (X = NO 3 (30), PF 6 (31), OTf (32)), [Ag 2 (8) 2 ]X 2 (X = NO 3 (33), PF 6 (34), OTf (35)) and [Ag 2 (10) 2 ]X 2 (X = NO 3 (39), PF 6 (40), OTf (41)), respectively, in good yields (Schemes 4-7). However, under similar reaction conditions, reaction of AgX (X = NO 3 , PF 6 , OTf) with 1 equiv of chiral N 4 -ligands 6 and 9 does not give the binuclear complexes, instead, a series of mono-nuclear ionic complexes [Ag(6)]X (X = NO 3 (27), PF 6 (28), OTf (29)) and [Ag (9)]X (X = NO 3 (36), PF 6 (37), OTf (38)) have been isolated, respectively, in good yields (Schemes 4 and 6). Complexes The single-crystal structure of complex 40 shows that there are well-separated, alternating layers of the complex cation [Ag 2 (10) 2 ] 2+ and two free anion PF 6 À and two solvated methanol molecules and two solvated H 2 O molecules in the lattice.…”
Section: Synthesis and Characterization Of Ag(i) Complexes With C 2 -mentioning
confidence: 99%
“…(R)-2,2 0 -Diamino-1,1 0 -binaphthyl [20,21], and (R)-6,6 0 -dimethylbiphenyl-2,2 0 -diamine [22] were prepared according to the literature methods. Infrared spectra were obtained from KBr pellets on an Avatar 360 Fourier transform spectrometer.…”
Section: General Methodsmentioning
confidence: 99%